Analysis Of The Role Of The Primary Sector On Employment Opportunities In Kalimantan Province - Haris Tonix Simanjuntak (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
The aims of this study are as follows: (1) To identify and analyze the influence of the Agriculture Sector, Forestry Sector, Fisheries Sector and Coal Mining Sector on Employment Opportunities in the Kalimantan region. Based on the analysis and research results, the following conclusions can be obtained: (1) Based on the estimation results of panel data with the Fixed Effect Model (FEM) it is explained that simultaneously the agricultural sector, forestry sector, fisheries sector and mining sector have a significant effect on employment opportunities in the Region Kalimantan. (2) Partially the results of panel data estimation using the Fixed Effect Model (FEM) explain that the agricultural sector, forestry sector, fisheries sector and mining sector have a significant effect on employment opportunities in the Kalimantan Region.